2002
DOI: 10.1002/1615-9861(200205)2:5<580::aid-prot580>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Identification of vaccine candidate antigens of Staphylococcus aureus by serological proteome analysis

Abstract: In this study we applied serological proteome analysis (Klade, C. S. et al. Proteomics 2001, 1, 890-898) for identification of bacterial vaccine candidate antigens. First, approximately one hundred sera from healthy individuals and patients suffering from Staphylococcus aureus infections were screened for antibodies against staphylococcal lysates and recombinant proteins representing surface antigens. Two pools (healthy donors, patients) each consisting of five sera with the highest antiproteinaceous IgG react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(108 citation statements)
references
References 29 publications
7
98
0
3
Order By: Relevance
“…SasI was also shown to be expressed during infection because sera from convalescent patients reacted with SasI peptides displayed on the surface of E. coli (Etz et al, 2002), while SdrD was identified by serological proteome analysis (Vytvytska et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…SasI was also shown to be expressed during infection because sera from convalescent patients reacted with SasI peptides displayed on the surface of E. coli (Etz et al, 2002), while SdrD was identified by serological proteome analysis (Vytvytska et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Now, highthroughput screening methods for antigen detection in microorganism proteomes have appeared. These include SERPA technology (SERological Proteome Analysis) and antigenome analysis (Klade, 2002;Ling et al, 2004;Tedeschi et al, 2009,Vytvytska et al, 2002, Målen et al, 2008Glowalla et al, 2009;Meinke et al, 2005;Felgner et al, 2009;Fritzer et al, 2010). The first method consists in the separation of protein components of the cultivated infectious agent by two-dimensional electrophoresis followed by subsequent visualization of antigenically active proteins by immunoblotting with antibodies from sera of patients with corresponding diseases (Målen et al, 2008;Glowalla et al, 2009;Meinke et al, 2005;Felgner et al, 2009;Fritzer et al, 2010).…”
Section: Selection Of Antigenic Determinants For Immunogenic Constructsmentioning
confidence: 99%
“…A total of 60 antigenic proteins were identified [46,47] Serological proteome analysis: A surface proteins preparation from S. aureus was resolved by 2D electrophoresis and analyzed in immunoblotting using two pools, each consisting of five sera coming from healthy donors or patients. Twenty-one spots were isolated analyzed in mass spectrometry allowing the identification of 15 proteins including known and new vaccine candidates [31] Porphyromonas gingivalis Periodontal pathogen that has been implicated in the etiology of chronic adult periodontitis…”
Section: Neisseria Meningitidis B Major Cause Of Bacterial Septicemiamentioning
confidence: 99%
“…Recently, advances in protein separation technologies, combined with mass spectrometry and genome sequencing, have made the elucidation of total protein components of a given cellular population a feasible task [27][28][29]. Moreover, the combination of proteomics with serological analysis has recently led to the development of a new valuable approach defined as serological proteome analysis (SERPA) for the identification of in vivo immunogens suitable as vaccine candidates (Table 2, [30,31]). …”
Section: Proteomic Analysismentioning
confidence: 99%